Exploring the Role of Plants in Bio-remediation: Harnessing Nature's Clean-up Agents - Sahoo, Monalisha (PT. Riset Press International, 2024)
The study investigates the vital role of plants in bio-remediation processes, capitalizing on their inherent ability to act as nature's clean-up agents. As industries continue to generate pollutants, there is a growing need for sustainable and eco-friendly approaches to mitigate environmental damage. This research delves into the diverse mechanisms by which plants contribute to bioremediation, including phytoremediation, rhizofiltration, and phytoextraction. The exploration encompasses the interactions between plant roots and soil microorganisms, as well as the potential for genetic modifications to enhance bio-remediation efficiency. By comprehensively analysing the scientific literature, this study aims to provide insights into harnessing the natural capabilities of plants for effective and environmentally friendly remediation strategies. The findings contribute to the on-going discourse on sustainable environmental management, offering promising avenues for the integration of plant-based solutions into mainstream bio-remediation practices.